Energy-saving low-carbon cement prepared from alkali-activated aluminum-containing solid waste and preparation method of energy-saving low-carbon cement
Energy-saving and low-carbohydrate cement is prepared by specific thermal activation treatment and combining specific raw material ratios and exciter modulus, which solves the problems of improper activation treatment and unreasonable activation control in the prior art, and achieves cement preparation with high activity index and low energy consumption.
Patent Information
- Application Number
- CN202411960183.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, due to inappropriate activation treatment of aluminum-containing solid waste and unreasonable control of the modulus of the exciter, the activity index of energy-saving and low-carbohydrate cement is not ideal.
The red mud is processed by a specific thermal activation temperature and time, combined with the specific raw material ratio and the exciter module, energy-saving and low-carbohydrate cement is prepared. The specific steps include thermal activation treatment of the red mud at 500-900°C for 30-60 minutes, mixing bauxite tailings, steel slag, desulfurization gypsum and exciter, ball milling and grinding, and controlling the specific surface area and screen margin.
The 28d activity index of energy-saving and low-carbon cement has reached more than 95%, ensuring the cement quality, reducing the carbon dioxide emissions from limestone calcination and low-temperature calcination consumption of coal resources, and reducing preparation costs.
Smart Images

Figure BDA0005216904090000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum-containing solid waste treatment, and in particular to energy-saving and low-carbon cement prepared from alkali-activated aluminum-containing solid waste and a preparation method thereof. Background Art
[0002] The energy-saving low-carbon cement studied in this application is similar to soil polymer cement. It is an alkali-activated cement with superior performance. It was first studied by Davadovits in France. It was prepared from powdered slag and used to produce precast concrete products. After that, Ma Hongwen et al. prepared mineral polymer materials using potassium feldspar tailings, metakaolinite, gold mine tailings, NaOH, etc., and effectively utilized mine tailings. Yan Fulu et al. used exogenous Na2O to stimulate the activity of red mud, and then added granulated blast furnace slag and cement to prepare cementitious materials, which improved the properties of flexural and compressive strength and drying shrinkage. Compared with traditional silicate cement, the biggest advantage of energy-saving low-carbon cement is that it does not require the use of limestone raw materials and does not require high-temperature calcination. Instead, it uses alkali activators to improve its various properties, greatly reducing the carbon dioxide gas emitted by calcination, saving energy, and helping to reduce environmental pollution.
[0003] Aluminum-containing solid waste, also known as aluminum solid waste, is solid waste discharged during the production of alumina, including red mud, bauxite tailings, etc. Red mud is solid waste discharged during the production of alumina, and bauxite tailings are residues produced during the flotation process of bauxite aluminum. With the advancement of resource utilization of aluminum-containing solid waste, the application of red mud, bauxite tailings, etc. in cement production has been studied accordingly.
[0004] For example: Patent No. 201210243405.9 discloses the use of waste slag fluorgypsum and red mud to prepare sulphoaluminate special cement clinker, and the raw material is prepared by mixing fluorgypsum, red mud, limestone and bauxite, which is then calcined in a rotary kiln, and obtained by rapid cooling and grinding. Clinker can achieve large-scale utilization of fluorgypsum and red mud that are difficult to handle in the fluorine industry and alumina industry, replacing the increasingly scarce natural mineral resources such as bauxite, limestone, gypsum, etc.
[0005] Another example: Patent No. 202010466982.9 discloses the use of red mud and other solid wastes (slag, slag, steel slag, desulfurized gypsum) mixed, and added activators and admixtures to prepare a grouting cementitious material. The material has a short setting time, high early strength, high mechanical strength of the stone body, excellent erosion resistance, and can alleviate the pressure of solid waste storage, solve the environmental pollution problem of red mud, achieve high added value, and promote the comprehensive utilization of red mud.
[0006] Another example: Patent No. 202210718738.6 discloses the use of stainless steel slag, red mud and calcium, carbon, silicon, aluminum (coal gasification residue, aluminum ash slag) and other raw materials, adding fluorinated gypsum, desulfurized gypsum, cement clinker, water reducer, cementitious materials, etc. to mix and prepare a composite cementitious material to solve the problems of harmlessness, reduction and resource utilization of industrial solid waste, agricultural solid waste and construction solid waste, and promote the coordinated utilization of multiple solid wastes and environmental protection.
[0007] Another example: Patent application No. 202310881940.5 discloses the use of cement clinker, mineral powder, fly ash, coal gangue, red mud, etc. as active components, slag, tailings, concrete fragments, aerated block fragments, etc. as filling components, and desulfurized gypsum, carbide slag, chemical agents, etc. as activator components to prepare low-carbon water-reducing cementitious materials, thereby achieving low carbon and ensuring the strength of the cementitious materials.
[0008] It can be seen that in the prior art, aluminum-containing solid waste (red mud, bauxite tailings) has been applied to the production of cementitious materials or cement clinker, etc., realizing the resource utilization of aluminum-containing solid waste and reducing the stockpile of aluminum-containing solid waste. However, in the prior art, due to improper activation treatment of aluminum-containing solid waste, unreasonable control of the modulus of the activator, and improper ratio of various raw materials, the 28d activity index of energy-saving and low-carbon cement is not ideal. Summary of the invention
[0009] Based on the above technical problems, the present invention provides an energy-saving and low-carbon cement prepared from alkali-activated aluminum-containing solid waste and a preparation method thereof.
[0010] The specific technical solution is:
[0011] One of the purposes of the invention is to provide energy-saving and low-carbon cement prepared by alkali-activated aluminum-containing solid waste, which is prepared by mixing the raw material components, in parts by mass, of 10-20 parts of bauxite tailings, 40-55 parts of red mud, 10-20 parts of steel slag, 10-15 parts of desulfurized gypsum, 10-15 parts of activator and 0-0.5 parts of triethanolamine; the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.0-2.0, and the red mud is heat-activated red mud obtained by heat activation treatment at 500-900°C for 30-60min.
[0012] Energy-saving low-carbon cement is produced by properly controlling the proportion of raw materials including bauxite tailings, red mud, steel slag, desulfurized gypsum, activator and / or triethanolamine, and selecting activators under specific modulus to match specific thermal activation treatment conditions for thermal activation treatment of red mud. The 28d activity index of the cement low-carbon cement reaches more than 95%, thereby ensuring the quality of the energy-saving low-carbon cement. At the same time, the emission of carbon dioxide due to the calcination of limestone is avoided, and the consumption of coal resources is reduced by low-temperature calcination, thereby reducing the cost of cement preparation.
[0013] In order to ensure that the 28d activity index of energy-saving low-carbon cement reaches 95%, it is preferred that the raw material components are prepared by mixing 10 parts of bauxite tailings, 50 parts of red mud, 15 parts of steel slag, 15 parts of desulfurized gypsum, and 10 parts of activator in parts by mass; the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.5, and the red mud is heat-activated red mud obtained by heat activation treatment at 700°C for 50 minutes.
[0014] More preferably, the raw material components are prepared by mixing 10 parts of bauxite tailings, 55 parts of red mud, 10 parts of steel slag, 10 parts of desulfurized gypsum, 14.5 parts of activator and 0.5 parts of triethanolamine in parts by mass; the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.5-1.8, and the red mud is heat-activated red mud obtained by heat activation treatment at 700-800°C for 40-60min.
[0015] More preferably, the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.8, and the red mud is heat-activated red mud obtained by heat activation treatment at 800°C for 40 min; more preferably, the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.5, and the red mud is heat-activated red mud obtained by heat activation treatment at 800°C for 60 min; more preferably, the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.5, and the red mud is heat-activated red mud obtained by heat activation treatment at 700°C for 50 min; more preferably, the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.5, and the red mud is heat-activated red mud obtained by heat activation treatment at 800°C for 40 min.
[0016] More preferably, the raw material components are prepared by mixing 15 parts of bauxite tailings, 40 parts of red mud, 20 parts of steel slag, 10 parts of desulfurized gypsum, 14.5 parts of activator and 0.5 parts of triethanolamine in parts by mass; the activator is a mixture of sodium hydroxide and water glass mixed into a modulus of 1.5 or 1.8, and the red mud is heat-activated red mud obtained by heat-activating at 800°C for 60 minutes. Preferably, the activator is a mixture of sodium hydroxide and water glass mixed into a modulus of 1.2, and the red mud is heat-activated red mud obtained by heat-activating at 500°C for 60 minutes.
[0017] More preferably, the raw material components are prepared by mixing 20 parts of bauxite tailings, 40 parts of red mud, 19.5 parts of steel slag, 10 parts of desulfurized gypsum, 10 parts of activator and 0.5 parts of triethanolamine in parts by mass; the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.5, and the red mud is heat-activated red mud obtained by heat activation treatment at 800°C for 60 minutes.
[0018] The second purpose of the invention is to provide a method for preparing energy-saving and low-carbon cement by using the above-mentioned alkali-activated aluminum-containing solid waste, comprising the following steps:
[0019] (1) heat-activating red mud at 500-900° C. for 30-60 min to obtain heat-activated red mud; and mixing sodium hydroxide and water glass to prepare a modulus of 1.0-2.0 to obtain an activator;
[0020] (2) grinding the bauxite tailings, thermally activated red mud, steel slag, and desulfurized gypsum separately by a ball mill, and then mixing and stirring to obtain a first mixed material;
[0021] (3) The first mixture is mixed with an activator or the first mixture is mixed with an activator and triethanolamine to obtain a second mixture; the second mixture is ground to a size of ≥5% passing through a 45 μm sieve and a specific surface area of 300 m2 / kg to 400 m2 / kg.
[0022] Compared with the prior art, the technical effects created by the present invention are embodied in:
[0023] The invention utilizes specific thermal activation temperature and thermal activation time to treat red mud, so that the stable silicon-aluminum structure in the red mud is destroyed and the activity is improved; by utilizing specific amounts of bauxite tailings, steel slag, desulfurized gypsum, activator and / or triethanolamine, and combining the activator with a specific modulus, the 28d activity index of energy-saving low-carbon cement can reach more than 95%, thereby ensuring the stable quality of the energy-saving low-carbon cement.
[0024] The invention has a simple creation process, is easy to operate, and realizes high-value resource utilization of aluminum-containing solid waste, which helps to accelerate the disposal of aluminum-containing solid waste (red mud, bauxite tailings, etc.) and reduce the stockpile volume. DETAILED DESCRIPTION
[0025] In order to facilitate those skilled in the art to correctly understand the present invention and enable those skilled in the art to fully understand the technical content of the present invention, the technical solution of the present invention is further explained below in conjunction with specific implementation methods. However, this explanation does not limit the scope of protection required for the present invention. The scope of protection of the present invention by those skilled in the art cannot be limited to the following explanations. Any equivalent substitutions or changes made by any those skilled in the art or persons familiar with the technology in the art based on the present invention and the technical solution and inventive concept thereof should be covered within the scope of protection of the present invention.
[0026] Example 1
[0027] The red mud is heat-activated at 800°C for 60 minutes to obtain heat-activated red mud; potassium hydroxide and water glass are mixed to prepare a mixture with a modulus of 1.5 to obtain an activator, and then 50 kg of heat-activated red mud, 10 kg of bauxite tailings, 15 kg of steel slag, and 15 kg of desulfurized gypsum are ground separately, and then mixed to obtain a first mixture; the first mixture is mixed with 10 kg of the activator to form a second mixture, and the second mixture is ground to a sieve residue of 45 μm sieve ≥5%, and the specific surface area is between 300 m2 / kg and 400 m2 / kg, so as to obtain energy-saving and low-carbon cement.
[0028] Example 2
[0029] On the basis of Example 1, other aspects are the same as Example 1, and the red mud is thermally activated at 700° C. for 50 min.
[0030] Example 3
[0031] The red mud is heat-activated at 800°C for 40 minutes to obtain heat-activated red mud; potassium hydroxide and water glass are mixed to prepare a mixture with a modulus of 1.8 to obtain an activator, and then 55 kg of heat-activated red mud, 10 kg of bauxite tailings, 10 kg of steel slag, and 10 kg of desulfurized gypsum are ground separately, and then mixed to obtain a first mixture; the first mixture is mixed with 14.5 kg of the activator and 0.5 kg of triethanolamine to form a second mixture, and the second mixture is ground to a sieve residue of 45 μm sieve ≥5%, and the specific surface area is between 300 m2 / kg and 400 m2 / kg, so as to obtain energy-saving and low-carbon cement.
[0032] Example 4
[0033] The red mud is heat-activated at 800°C for 60 minutes to obtain heat-activated red mud; potassium hydroxide and water glass are mixed to prepare a mixture with a modulus of 1.0 to obtain an activator, and then 40 kg of heat-activated red mud, 15 kg of bauxite tailings, 20 kg of steel slag, and 10 kg of desulfurized gypsum are ground separately, and then mixed to obtain a first mixture; the first mixture is mixed with 14.5 kg of the activator and 0.5 kg of triethanolamine to form a second mixture, and the second mixture is ground to a sieve residue of 45 μm sieve ≥5%, and the specific surface area is between 300 m2 / kg and 400 m2 / kg, so as to obtain energy-saving and low-carbon cement.
[0034] Example 5
[0035] On the basis of Example 4, the other steps are the same as Example 4, potassium hydroxide and water glass are mixed to prepare a mixture with a modulus of 1.2 to obtain an activator.
[0036] Example 6
[0037] On the basis of Example 5, the other steps are the same as Example 5, and the red mud is thermally activated at 500° C. for 60 min to obtain thermally activated red mud.
[0038] Example 7
[0039] On the basis of Example 4, the other steps are the same as Example 4, potassium hydroxide and water glass are mixed to prepare a mixture with a modulus of 1.5 to obtain an activator.
[0040] Example 8
[0041] On the basis of Example 4, the other steps are the same as Example 4, potassium hydroxide and water glass are mixed to prepare a mixture with a modulus of 1.8 to obtain an activator.
[0042] Example 9
[0043] On the basis of Example 4, the other steps are the same as Example 4, potassium hydroxide and water glass are mixed to prepare a mixture with a modulus of 2.0 to obtain an activator.
[0044] Example 10
[0045] The red mud is heat-activated at 800°C for 60 minutes to obtain heat-activated red mud; potassium hydroxide and water glass are mixed to prepare a mixture with a modulus of 1.5 to obtain an activator, and then 40 kg of heat-activated red mud, 20 kg of bauxite tailings, 19.5 kg of steel slag, and 10 kg of desulfurized gypsum are ground separately, and then mixed to obtain a first mixture; the first mixture is mixed with 10 kg of the activator and 0.5 kg of triethanolamine to form a second mixture, and the second mixture is ground to a sieve residue of 45 μm sieve ≥5%, and the specific surface area is between 300 m2 / kg and 400 m2 / kg, so as to obtain energy-saving and low-carbon cement.
[0046] Embodiment 11
[0047] The red mud is heat-activated at 800°C for 60 minutes to obtain heat-activated red mud; potassium hydroxide and water glass are mixed to prepare a mixture with a modulus of 1.5 to obtain an activator, and then 60 kg of heat-activated red mud, 10 kg of bauxite tailings, 10 kg of steel slag, and 10 kg of desulfurized gypsum are ground separately, and then mixed to obtain a first mixture; the first mixture is mixed with 10 kg of the activator to form a second mixture, and the second mixture is ground to a 45 μm sieve residue of ≥5%, and the specific surface area is between 300 m2 / kg and 400 m2 / kg, so as to obtain energy-saving and low-carbon cement.
[0048] Example 12
[0049] On the basis of Example 11, the other steps are the same as Example 11, red mud is heat-activated at 900° C. for 30 min to obtain heat-activated red mud; potassium hydroxide and water glass are mixed to prepare a mixture with a modulus of 2.0 to obtain an activator.
[0050] Embodiment 13
[0051] The red mud is heat-activated at 500°C for 60 minutes to obtain heat-activated red mud; potassium hydroxide and water glass are mixed to prepare a mixture with a modulus of 1.5 to obtain an activator, and then 55 kg of heat-activated red mud, 10 kg of bauxite tailings, 14.5 kg of steel slag, and 10 kg of desulfurized gypsum are ground separately, and then mixed to obtain a first mixture; the first mixture is mixed with 10 kg of the activator and 0.5 kg of triethanolamine to form a second mixture, and the second mixture is ground to a sieve residue of 45 μm sieve ≥5%, and the specific surface area is between 300 m2 / kg and 400 m2 / kg, so as to obtain energy-saving and low-carbon cement.
[0052] Embodiment 14
[0053] On the basis of Example 13, the rest is the same as Example 13, and the red mud is thermally activated at 800° C. for 60 min to obtain thermally activated red mud.
[0054] Embodiment 15
[0055] Based on Example 13, the other steps are the same as Example 13, and the red mud is thermally activated at 900° C. for 30 min to obtain thermally activated red mud.
[0056] Example 16
[0057] On the basis of Example 13, the rest are the same as Example 13, and the red mud is thermally activated at 700° C. for 50 min to obtain thermally activated red mud.
[0058] Embodiment 17
[0059] On the basis of Example 13, the rest is the same as Example 13, and the red mud is thermally activated at 800° C. for 40 min to obtain thermally activated red mud.
[0060] The samples prepared in Examples 1 to 17 were tested for fineness (residue after passing through a 45 μm sieve), 28d activity index (with P·O42.5 cement as a reference), and stability (boiling method). Each set of data was tested three times and the average value was taken. The results are recorded in the following Table 1:
[0061] Table 1
[0062]
[0063] Note:
[0064] ① The fineness detection of the invention refers to GB / T1345-2023 (screening method).
[0065] ② The activity index test refers to GB / T17671-1999, and the 28d compressive strength of the sample prepared by using ordinary Portland cement 52.5 purchased on the market as the reference cement is 54.6MPa.
[0066] ③ Stability test shall refer to GB / T1346-2011 (boiling method).
[0067] It can be seen from Table 1 that: by comparing Example 1 with Example 2, Example 5 with Example 9, and Example 13 to Example 17, it can be seen that when the raw material ratio and the modulus of the activator are the same, the change of the thermal activation temperature and the thermal activation time will cause the energy-saving low-carbon cement activity index to change; by comparing Example 10 with Example 11, it can be seen that when the thermal activation temperature, the thermal activation time and the modulus of the activator are the same, the change of the raw material ratio will cause the energy-saving low-carbon cement activity index to change; by comparing Example 4 to Example 8, it can be seen that when the thermal activation temperature, the thermal activation time and the raw material ratio are the same, the change of the activator modulus will cause the energy-saving low-carbon cement activity index to change. The number changes; by comparing Example 11 and Example 12, it can be seen that under the same raw material ratio, changes in the activator modulus, thermal activation temperature, thermal activation time, etc. will cause the energy-saving low-carbon cement activity index to change; by comparing Example 1 and Example 3, it can be seen that under the same thermal activation temperature, changes in the thermal activation temperature, activator modulus, and raw material ratio will cause the energy-saving low-carbon cement activity index to change; by comparing Example 1, Example 2, Example 11, Example 12 with Examples 3 to 10 and Examples 13 to 17, it can be seen that the addition of triethanolamine will help to improve the activity index of energy-saving low-carbon cement.
[0068] In summary, the present invention uses heat-activated red mud, bauxite tailings, steel slag, desulfurized gypsum, activator and / or triethanolamine as raw materials to prepare energy-saving low-carbon cement, uses specific heat activation temperature and heat activation time to treat red mud to obtain heat-activated red mud, and then mixes and grinds the heat-activated red mud with bauxite tailings, steel slag, desulfurized gypsum, activator and / or triethanolamine to prepare energy-saving low-carbon cement, and controls it in combination with specific raw material ratios and specific activator modulus, effectively stimulating the mutual synergy of various raw materials, improving the activity index of energy-saving low-carbon cement, and making the 28d activity index reach more than 95%. Specifically embodied in:
[0069] (1) Under the raw material ratio in Example 3, when the red mud thermal activation temperature is controlled to 800°C for 40 min and the activator modulus is 1.8, the 28d activity index of the energy-saving low-carbon cement reaches more than 95%.
[0070] (2) Under the raw material ratios of Examples 4 to 9, when the red mud thermal activation temperature is controlled to 800°C for 60 min and the activator modulus is 1.5 or 1.8, the 28d activity index of the energy-saving low-carbon cement reaches more than 95%.
[0071] (3) Under the raw material ratios of Examples 4 to 9, when the red mud thermal activation temperature is controlled to be 500°C for 60 min and the activator modulus is 1.2, the 28d activity index of the energy-saving low-carbon cement reaches more than 95%.
[0072] (4) Under the raw material ratio of Example 10, when the red mud thermal activation temperature is controlled to 800°C for 60 min and the activator modulus is 1.5, the 28d activity index of the energy-saving low-carbon cement reaches more than 95%.
[0073] (5) Under the raw material ratios of Examples 13 to 17, when the thermal activation temperature of red mud is controlled to be 800°C for 60 min, or 800°C for 40 min, or 700°C for 50 min, and the activator modulus is 1.5, the 28d activity index of energy-saving and low-carbon cement reaches more than 95%.
[0074] The invention creates heat-activated red mud by treating red mud containing aluminum solid waste at a specific heat activation temperature for a specific time, and combines a specific raw material ratio and a specific activator modulus control, so that the 28d activity index of energy-saving low-carbon cement prepared with heat-activated red mud, bauxite tailings, steel slag, desulfurized gypsum, activator and / or triethanolamine as raw materials reaches more than 95%, ensuring the quality of energy-saving low-carbon cement prepared with raw materials such as aluminum solid waste (red mud, bauxite tailings). In addition, limestone is avoided as a raw material, which reduces the emission of a large amount of carbon dioxide during the limestone calcination process. At the same time, red mud is thermally activated at a lower temperature, which reduces the energy consumption of low-carbon cement preparation.
[0075] The samples obtained in the invention are tested with reference to GB6566-2010 "Limits of Radioactive Nuclides in Building Materials", and it is known that the internal radiation index of the obtained energy-saving low-carbon cement is I Ra ≤0.3, and external radiation index I r ≤0.7, which meets the radioactivity limit standard requirements for building materials.
[0076] Other matters not covered by the present invention may be achieved by conventional technical means with reference to the prior art or common knowledge known to those skilled in the art, for example, using a ball mill or a pulverizer as a grinding or pulverizing device and a method for operating the grinding or pulverizing device.
Claims
1. An energy-saving and low-carbon cement prepared from alkali-activated aluminum-containing solid waste, characterized in that: The red mud is prepared by mixing the raw material components, in parts by mass, of 10-20 parts of bauxite tailings, 40-55 parts of red mud, 10-20 parts of steel slag, 10-15 parts of desulfurized gypsum, 10-15 parts of activator and 0-0.5 parts of triethanolamine; the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.0-2.0, and the red mud is heat-activated red mud obtained by heat activation treatment at 500-900°C for 30-60 minutes.
2. The energy-saving and low-carbon cement prepared by alkali-activated aluminum-containing solid waste as claimed in claim 1, characterized in that: The raw material components are prepared by mixing 10 parts of bauxite tailings, 50 parts of red mud, 15 parts of steel slag, 15 parts of desulfurized gypsum, and 10 parts of activator in parts by mass; the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.5, and the red mud is heat-activated red mud obtained by heat activation treatment at 700°C for 50 minutes.
3. The energy-saving and low-carbon cement prepared by alkali-activated aluminum-containing solid waste as claimed in claim 1, characterized in that: The raw material components are prepared by mixing 10 parts of bauxite tailings, 55 parts of red mud, 10 parts of steel slag, 10 parts of desulfurized gypsum, 14.5 parts of activator and 0.5 parts of triethanolamine in parts by mass; the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.5-1.8, and the red mud is heat-activated red mud obtained by heat activation treatment at 700-800°C for 40-60 minutes.
4. The energy-saving and low-carbon cement prepared by alkali-activated aluminum-containing solid waste as claimed in claim 3, characterized in that: The activator is a mixture of sodium hydroxide and water glass with a modulus of 1.8, and the red mud is heat-activated red mud obtained by heat activation treatment at 800° C. for 40 minutes; Or the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.5, and the red mud is heat-activated red mud obtained by heat activation treatment at 800° C. for 60 minutes; Or the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.5, and the red mud is heat-activated red mud obtained by heat activation treatment at 700° C. for 50 minutes; Or the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.5, and the red mud is heat-activated red mud obtained by heat activation treatment at 800°C for 40 minutes.
5. The energy-saving and low-carbon cement prepared by alkali-activated aluminum-containing solid waste as claimed in claim 1, characterized in that: The raw material components are prepared by mixing 15 parts of bauxite tailings, 40 parts of red mud, 20 parts of steel slag, 10 parts of desulfurized gypsum, 14.5 parts of activator and 0.5 parts of triethanolamine in parts by mass; the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.5 or 1.8, and the red mud is heat-activated red mud obtained by heat activation treatment at 800°C for 60 minutes.
6. The energy-saving and low-carbon cement prepared by alkali-activated aluminum-containing solid waste as claimed in claim 5, characterized in that: The activator is a mixture of sodium hydroxide and water glass with a modulus of 1.2, and the red mud is heat-activated red mud obtained by heat activation treatment at 500° C. for 60 minutes.
7. The energy-saving and low-carbon cement prepared by alkali-activated aluminum-containing solid waste as claimed in claim 1, characterized in that: The raw material components are prepared by mixing 20 parts of bauxite tailings, 40 parts of red mud, 19.5 parts of steel slag, 10 parts of desulfurized gypsum, 10 parts of activator and 0.5 parts of triethanolamine in parts by mass; the activator is a mixture of sodium hydroxide and water glass with a modulus of 1.5, and the red mud is heat-activated red mud obtained by heat activation treatment at 800°C for 60 minutes.
8. The method for preparing energy-saving and low-carbon cement by using alkali-activated aluminum-containing solid waste as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: (1) heat-activating red mud at 500-900° C. for 30-60 min to obtain heat-activated red mud; and mixing sodium hydroxide and water glass to prepare a modulus of 1.0-2.0 to obtain an activator; (2) grinding the bauxite tailings, thermally activated red mud, steel slag, and desulfurized gypsum separately by a ball mill, and then mixing and stirring to obtain a first mixed material; (3) The first mixture is mixed with an activator or the first mixture is mixed with an activator and triethanolamine to obtain a second mixture; the second mixture is ground to a size of ≥5% passing through a 45 μm sieve and a specific surface area of 300 m2 / kg to 400 m2 / kg.
Citation Information
Patent Citations
Method for preparing sulphoaluminate special cement clinker from waste residue fluorine gypsum and red mud
CN102765893A
A multi-source solid waste-based grouting cementitious material, its preparation method and application
CN111689752B
Method for preparing composite cementing material by utilizing tailings after iron extraction of multi-element solid waste
CN115159875A
Low-carbon water-reducing cementing material and preparation method thereof
CN116874209A
Cited By
Solid waste-based iron aluminate cement and preparation method thereof
CN122403802A